Effects of Melagatran, a New Low-molecular-weight Thrombin Inhibitor, on Thrombin and Fibrinolytic Enzymes - Gustafsson, D.; Antonsson, T.; Bylund, R.; Eriksson, U.; Gyzander, E.; Nilsson, I.; Elg, M.; Mattsson, C.; Deinum, J.; Pehrsson, S.; Karlsson, O.; Nilsson, A.; Sörensen, H. (Thrombosis and Haemostasis, 1998)
Melagatran, a new, competitive and rapid inhibitor of thrombin with a molecular mass of 429 Da is described. Melagatran is well tolerated when administered in very high doses, and the oral bioavailability in the dog is relatively high. The aim of the study was to determine, in the preclinical setting, the degree of selectivity against the fibrinolytic system required for entering the clinical development phase. Melagatran was compared with two structurally similar thrombin inhibitors, inogatran and H 317/86. The potent inhibition of thrombin by melagatran was demonstrated by a low inhibition constant (Ki) for thrombin (0.002 μmol/l) and prolongation of clotting time to twice the control value in coagulation assays at low concentrations (0.010, 0.59 and 2.2 μmol/l for thrombin time, activated partial thromboplastin time and prothrombin time, respectively). Furthermore, thrombin-induced platelet aggregation was inhibited at the same concentration (IC50-value 0.002 μmol/l) as the Ki-value for thrombin. In two assays of global fibrinolysis, inhibition was observed at a concentration of 1.1 μmol/l in a euglobulin plasma fraction model, while no inhibition was observed at a concentration of ≤10 μmol/l in a plasma model. In an in vivo model of endogenous fibrinolysis in the rat, inhibition of fibrinolysis was observed at ≥1.0 μmol/l. In all assays, except the Ki-ratio determinations, the compounds could be graded with regard to selectivity against the fibrinolytic system: inogatran > melagatran > H 317/86. For melagatran, inhibition of fibrinolysis was not observed at concentrations below the upper limit of the proposed therapeutic plasma concentration interval (<0.5 μmol/l). Thus, melagatran seems to have a sufficient selectivity against the fibrinolytic system, while H 317/86 was considered to be insufficient for clinical development.